Qur'anic literacy in the protection of children's and women's rights in Muslim families - Saputra, Novendri Eka; Ismail, Hidayatullah (Privietlab, 2025)
Violence, discrimination, and injustice against children and women in Muslim families remain a social problem of concern. One of the root problems is the low level of understanding of the values of the Qur'an, which actually contains the principles of protection, compassion, and justice for all family members. This study aims to examine the concept of Qur'anic literacy as an instrument for fostering awareness and practice of protecting the rights of children and women in Muslim families. Using a qualitative approach based on library research, this study traces relevant verses of the Qur'an, such as QS. An-Nisa', QS. Luqman, and QS. Al-Ahzab, as well as studying classical and contemporary scholars' interpretations of the values of justice ('adl), compassion (rahmah), and respect for human dignity (karamah insaniyyah). The study’s results show that Qur'anic literacy not only includes the ability to read and understand texts, but also includes the internalization of values and their application in family life. Strong Qur'anic literacy encourages the creation of balanced family relationships between rights and obligations, as well as a moral foundation for preventing violence and violations of the rights of children and women. Therefore, strengthening Qur'anic literacy needs to be integrated into family education, Islamic educational institutions, and socio-religious policies to realize a just, harmonious, and civilized Muslim family.